The Effectiveness of Public Speaking Training with Cognitive Behavioral Therapy for Public Speaking Anxiety among both Gender - Lestari, Anisa Indah; Noviekayati, IGAA; Saragih, Sahat (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
The purpose of this study was to examine the effectiveness of public speaking training with cognitive behavioral therapy towards public speaking anxiety. Another purpose was to examine the difference of this training effectiveness towards both genders, male and female. The training method is appropriate for applying cognitive behavioral approaches because this method aims to change cognition and to train certain behaviors for an individual to the adaptive and better behavior. The purposive sampling is used in this experimental research to obtain 20 samples including 10 males and 10 females sit in the third grade of a senior high class of TrubusIman Islamic Boarding School and have public speaking anxiety in the medium and high level.  The method used quantitative approach for analyzing data. It can be concluded that the training had been effectively minimizing public speaking anxiety but this research could not able show the difference of the training effectiveness among both genders.